LITERASI TENTANG DEMOKRASI DAN KEBUDAYAAN DI INDONESIA - Thomas Tokan Pureklolon (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
Democracy is a government in the hands of the people. Culture is something that will affect the level of knowledge, including a system of ideas or ideas contained in the human mind, so that in everyday life culture is abstract. Democracy culture is essentially a culture that puts the interests of the community first in making state policy decisions. Culture that has reached a certain point where the community can be called a civil society that upholds human values. The method used in writing this article is a qualitative method of library research with an interdisciplinary approach. What is imagined in this paper is that the basic principle of democracy in Indonesia is deliberation for consensus. The principle of deliberation contains a process dimension, while the principle of consensus contains a goal dimension in the political process in Indonesia.